(untitled) (Jurnal Manajemen Pemasaran, 2022)
For almost two years, the restrictions imposed by the government of Indonesia to control the spread of Covid-19 pandemic have changed the way consumers shopping their necessities from conventional shops to online stores. Supported with good information communication technology infrastructures and vast network of logistic distribution, customers find conveniences while shopping online, thus, e-commerce rules over the conventional businesses. As the pandemic was under control, conventional businesses resume their activities, including the opening of malls and other public places by the fourth quarter of 2021. As a result, shoppers are returning to malls, and shop owners are launching marketing campaigns to attract buyers. The aim of this study is to examine the influence of shopping enjoyment and in-store shopping experience on impulse buying among the Generation Y while browsing in-store on limited edition sport shoes. Limited edition sport shoes are purchased by the Generation Y sport fans as collectible items which become a symbol of social identity embedded to that generation. Previous studies noted that the Generation Y often conducted unplanned shopping while hanging out in the malls. With the new normal in-store shopping opportunity, it is expected that shopping enjoyment will stimulate the urge to buy impulsively among the Generation Y. As this is a quantitative research, the data are collected using questionnaires which are distributed to 300 respondents. The questionnaire gathers data on shopping enjoyment, impulse buying tendency, in-store browsing, and impulse buying from the Generation Y. Then, the data are processed with a smart PLS software to obtain the validity and reliability tests, and to prove the hypothesis test. The results show that shopping enjoyment and impulse buying tendency have a positive significant impact on in-store browsing, and in-store browsing has a positive significant impact on impulse buying. However, the variable of shopping enjoyment brings more impact to impulse buying than the variable of impulse buying tendency.